An Improved Jackson Inequality for the Best Trigonometric Approximation - Draganov, B. R. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
The paper presents an improved Jackson inequality and the corresponding inverse inequality for the best trigonometric approximation in terms of the moduli of smoothness equivalent to zero on the trigonometric polynomials whose degree does not exceed a certain number. The deduced inequalities are analogous to Timan’s inequalities. The relations between the moduli of different orders are also considered.